Eucalyptus oil inhalation–induced seizure: A novel, underrecognized, preventable cause of acute symptomatic seizure. Issue 3 (4th July 2017) - Mathew, Thomas; Kamath, Vikram; Kumar, R. Shiva; Srinivas, Meghana; Hareesh, Prarthana; Jadav, Rakesh; Swamy, Sreekanta
Summary: Eucalyptus oil (EO) is an essential oil that is widely used across the globe as an over‐the‐counter remedy for common ailments. EO‐induced seizure (EOIS) has not been recognized as an entity, and physicians rarely ask the history of exposure to eucalyptus oil when seeing a patient with first episode of seizure. Here we report 10 cases of EO inhalation–induced seizures seen over the past 2 years in three tertiary care hospitals. Eight patients had GTCS and two had CPS. We aim to raise awareness of seizures induced by exposure to eucalyptus oil.